Crime, Isolation, and Law Enforcement - Marcel Fafchamps; Christine Moser (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper investigates the relationship between criminal activity and geographical isolation. Using data from Madagascar, we show that, after we control for population composition and risk factors, crime increases with distance from urban centers and, with few exceptions, decreases with population density. In Madagascar, crime and insecurity are associated with isolation, not urbanization. This relationship is not driven by placement of law enforcement personnel which is shown to track crime, but fails to reduce feelings of insecurity in the population. Other risk factors have effects similar to those discussed in the literature on developed countries. We find a positive association between crime and the presence of law enforcement personnel, probably due to reporting bias. Law enforcement personnel helps solve crime but appears unable to prevent it.
Keywords: 330; criminal activity; distance from city; rule of law